ANGI-08. AN ANNEXIN A2-REGULATED PHENOTYPIC SHIFT IN GLIOMA. (11th November 2019) - Matsumoto, Yuji; Ichikawa, Tomotsugu; Kurozumi, Kazuhiko; Otani, Yoshihiro; Fujimura, Atsushi; Fujii, Kentaro; Shimazu, Yosuke; Tomita, Yusuke; Hattori, Yasuhiko; Uneda, Atsuhito; Tsuboi, Nobushige; Kaneda, Keisuke; et al.
Abstract: BACKGROUND: Malignant glioma has a poor prognosis and is characterized by excessive proliferation, invasion, and angiogenesis. Previously, we established subclones of glioma cell lines with different invasive phenotypes to investigate the mechanisms of invasion in this malignancy. That study revealed annexin A2 (ANXA2) as an activator of angiogenesis and perivascular invasion. Here, we investigated the molecular mechanism of the phenotypic shift in glioma that is induced by ANXA2. METHODS: We identified ANXA2 target genes using microarray analyses of our four established cell lines and RNA-seq data from the IVY Glioblastoma Atlas Project. Co-expression was then confirmed in human glioma cells. Additionally, qRT-PCR, immunoblotting, invasion assays, proliferation assays, and tube formation assays were performed to uncover the specific roles of these angiogenic invasion-related genes. Furthermore, we examined survival times and phenotypic shifts in vivo. RESULTS: We identified oncostatin M receptor (OSMR) as an ANXA2-target gene using microarray and RNA-seq, and confirmed its expression correlated with ANXA2 in glioma cells. ANXA2-overexpressing glioma cells showed enhanced OSMR expression and STAT3 phosphorylation, while STAT3 knockdown reduced OSMR expression. When ANXA2 was overexpressed in glioma cells, invasion, angiogenesis, proliferation, and epithelial-mesenchymal transition were promoted; however, silencing OSMR attenuated the ANXA2-induced phenotypic shift. In vivo, ANXA2-overexpressing glioma cells shortened the survival time of tumor-bearing mice, whereas OSMR knockdown increased survival times. CONCLUSIONS: We analyzed genes whose expression was regulated by ANXA2 in glioma using invasive glioma models. Through this analysis, we identified that ANXA2 and OSMR regulate a phenotypic shift, suggesting that OSMR could be a promising target to treat and prevent glioma invasion.